2021
DOI: 10.1016/j.janxdis.2021.102454
|View full text |Cite
|
Sign up to set email alerts
|

Fear and anxiety in the face of COVID-19: Negative dispositions towards risk and uncertainty as vulnerability factors

Abstract: In the face of the COVID-19 pandemic it is important to identify factors that make people particularly vulnerable of developing mental-health issues in order to provide case-specific treatments. In this article, we examine the roles of two psychological constructs – originally put forth in the behavioral decision sciences – in predicting interindividual differences in fear responses: general risk aversion (GRA) and intolerance of uncertainty (IU). We first provide a review of these constructs and illustrate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 99 publications
4
38
0
3
Order By: Relevance
“…Specifically, IU predicts concerns about COVID-19 spreading (Wheaton et al, 2021), viral contamination fear and social distancing fear (Fedorenko et al, 2021), and level of worry surrounding contracting COVID-19 (Tull et al, 2020). IU is also related to overall COVID-19-related stress (Paluszek et al, 2021) and body vigilance (Fedorenko et al, 2021) and is associated with fear of COVID-19 (Akbari et al, 2021;Bakioglu et al, 2020;Deniz, 2021;Mertens et al, 2020;Millroth & Frey, 2021;Paluszek et al, 2021;Satici et al, 2020;Voitsidis et al, 2020; but see Sauer et al, 2020 for a dissenting finding).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, IU predicts concerns about COVID-19 spreading (Wheaton et al, 2021), viral contamination fear and social distancing fear (Fedorenko et al, 2021), and level of worry surrounding contracting COVID-19 (Tull et al, 2020). IU is also related to overall COVID-19-related stress (Paluszek et al, 2021) and body vigilance (Fedorenko et al, 2021) and is associated with fear of COVID-19 (Akbari et al, 2021;Bakioglu et al, 2020;Deniz, 2021;Mertens et al, 2020;Millroth & Frey, 2021;Paluszek et al, 2021;Satici et al, 2020;Voitsidis et al, 2020; but see Sauer et al, 2020 for a dissenting finding).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that fear of COVID-19 can cause anxiety, depression and other mental diseases (Fitzpatrick et al, 2020;Nicomedes and Avila, 2020;Stein, 2020;Millroth and Frey, 2021; 10.3389/fpsyg.2022.996486…”
Section: Discussionmentioning
confidence: 99%
“…During the past two challenging years, the world has been through many difficult moments, many of them caused by the COVID-19 breakout. As a result, high levels of uncertainty marked these past COVID-19 years, along with fear, worry, anxiety, and general psychological distress (e.g., Deniz, 2021 ; Millroth and Frey, 2021 ; Voitsidis et al, 2021 ; Del-Valle et al, 2022 ). Since its outbreak, the COVID-19 pandemic has infected more than 490,000,000 people worldwide, and over 6.1 million COVID-19 deaths have been reported ( Worldmeter, 2022 ).…”
Section: Introductionmentioning
confidence: 99%